Nearly Comonotone Approximation of Periodic Functions (Analysis in Theory and Applications, 2017)
Suppose that a continuous $2π$-periodic function $f$ on the real axis changes its monotonicity at points $y_i: -π\le y_{2s}< y_{2s-1}< …< y_1
Keywords: Periodic functions; comonotone approximation; trigonometric polynomials; Jackson-type estimates.